(untitled) (PerCursos, 2025)
Beach sport in Uruguay origins in an economic and political context in which practices related to the advance of neoliberalism are consolidated. In this way, analyzing the speeches of the athletes who are members of the official Uruguayan beach handball delegation made it possible to point out the hybridization that the beach suffers from the emerging sports practices that take place there, as well as the implications of the configuration of said territory on occasion. of the relationship with the body that the players establish. The updates of the cultural industry after the digital revolution of the 90s created new ways of relating to the body and being an athlete. In this scenario, self-entrepreneurship in sport is in solidarity with the technical possibilities and economic updates that are particularly evident in the study of high-performance beach handball in Uruguay.